Lightweight handover control function (L-HCF) for Mobile Internet Protocol version Six (IPv6) - Mokhtar, Rania A.; Ismail, Ahmad Fadzil; Hasan, Mohammad Kamrul; Hashim , Wahidah; Abbas, Hajir; Saeed, Rashid A.; Islam, Shayla (Informatics (India) Ltd., 2015)
While shifting from one specific single access point to another point, the Mobile IP address permits a single mobile node for keeping an uninterrupted connection with the internet. Nevertheless, when handover occurs, the packets designed for the mobile nodes may have some delay or the risk of getting lost, because of the operations such as Mobile IP handover and link switching delay. This paper presented a novel control function that is called Lightweight Handover Control Function (L-HCF). The purpose of this control function is to improve of the handover performance in the perspective of Mobile IPv6 over wireless networks. The L-HCF functionality allows a router to choose which Access Router(AR)/Access Point (AP)/address that the mobile node is associated with when movement is needed, by using available IP addresses in its database if the movement operation in side domain or by exchange messages between other routers if the movement alter domain. Thus the Mobile Nodes (MN) can use this address without engaging in the process of Stateless Address Auto-configuration or the procedure of Duplicate Address Detection. The function is implemented analytically then simulated in OPNET. The result shows that, the control function offer minimum latency, less packet loss compared with the standard function of the mobile IPv6